Human ventilatory response to acute hyperoxia during and after 8 h of both isocapnic and poikilocapnic hypoxia. - Tansley, J; Clar, C; Pedersen, M; Robbins, P (1997)
During 8 h of either isocapnic or poikilocapnic hypoxia, there may be a rise in ventilation (VE) that cannot be rapidly reversed with a return to higher PO2 (L. S. G. E. Howard and P. A. Robbins. J. Appl. Physiol. 78:1098-1107, 1995). To investigate this further, three protocols were compared: 1) 8-h isocapnic hypoxia [end-tidal PCO2 (PETCO2) held at prestudy value, end-tidal PO2 (PETO2) = 55 Torr], followed by 8-h isocapnic euoxia (PETO2 = 100 Torr); 2) 8-h poikilocapnic hypoxia followed by 8-h poikilocapnic euoxia; and 3) 16-h air-breathing control. Before and at intervals throughout each protocol, the VE response to eucapnic hyperoxia (PETCO2 held 1-2 Torr above prestudy value, PETO2 = 300 Torr) was determined. There was a significant rise in hyperoxic VE over 8 h during both forms of hypoxia (P < 0.05, analysis of variance) that persisted during the subsequent 8-h euoxic period (P < 0.05, analysis of variance). These results support the notion that an 8-h period of hypoxia increases subsequent hyperoxic VE, even if acid-base changes have been minimized through maintenance of isocapnia during the hypoxic period.